Synthesis and Structures of Two Mononuclear Cu(II) Complexes Derived from 3-Methoxysalicylaldehyde Benzoylhydrazide Ligand - Peng Wang1, Yu; Hui Li1, Yun; Wei Zhang2, Hong; Gao1, Ying; Yun Yang1, Xiu (Asian Journal of Chemistry, 2014)
Reaction of 3-methoxysalicylaldehyde benzoylhydrazide (H2L) with Cu(ClO4)2·6H2O and heterocycle(imidazole or pyrazol) in methanol results in the formation of two isostructural mononuclear Cu(II) complexes, in which the metal ion is coordinated to the hydrazine-N, carbonyl-O and deprotonated phenolate-O of H2L and the imine-N atom of the neutral heterocycle, forming a distorted square-planar coordination configuration. In the crystal structure of complexes 1 and 2, the uncoordinated perchlorate anion is involved in forming intramolecular hydrogen bond. Additionally, complex 2 forms a centrosymmetric dimeric species due to weak apical coordination of the phenolate-O in a reciprocal fashion.